Modeling Demand for Money in Nepal - Kharel, Ram Sharan; Koirala, Tap Prasad (Economic Journal of Nepal, 2015)
In this paper, we estimate money demand functions for Nepal employing Johansen's tri-variate Conintegration method for the period of 1974/75-2009/10. In line with the previous studies, both narrowly defined real money demand () and broadly defined real money demand () are found to be a stable and predictable function of real income and interest rate albeit disequilibrium corrects more rapidly in  compared to . We reject the null hypothesis that income elasticity of money in both functions is unitary with satisfying homogeneous postulates. Further, we reject the null hypothesis that long run determinants of  and  are weakly exogenous. Based on these findings, we conclude that money demand functions are useful for conducting monetary policy in Nepal. Economic Journal of NepalVol. 34, No. 2, Issue no. 134, 2011